Early postpartum pelvic floor changes in primiparous women after vaginal delivery using 3T MRI. Issue 8 (21st February 2017) - Alt, Céline D.; Hampel, Franziska; Radtke, Jan Philipp; Hallscheidt, Peter; Schlehe, Bettina; Sohn, Christof; Brocker, Kerstin A.
Abstract : AIMS: Detection of early morphological pelvic floor changes after vaginal delivery in primiparous women using 3 Tesla magnetic resonance imaging. METHODS: A 3 Tesla magnetic resonance imaging was performed using static T2‐weighted turbo spin echo (tse) in three planes, T2‐weighted tse fat saturated and T1‐weighted sequence in transverse plane. All visible changes of pelvic structures (edema, hematoma, tear, or avulsion) were documented. Measurements for the integrity of the pelvic floor were performed and compared to a nulliparous control‐group. Differences in pelvic floor parameters were analyzed using an unpaired t ‐test. P <0.05 was considered statistically significant. RESULTS: Twenty‐five primiparous women delivered vaginally at term and underwent postpartum magnetic resonance imaging. Several morphological changes in the pelvis, superficial as well as deep, were detected in all participants. Anteroposterior hiatus, hiatal circumference, hiatal area, laterolateral hiatus, maximum muscle thickness, and levator urethra gap were significantly different to the nulliparous control‐group. CONCLUSIONS: Two‐dimensional 3 Tesla magnetic resonance imaging is feasible in a clinical and early postpartum setting establishing a reliable diagnostic tool to evaluate numerous morphological pelvic floor changes and the integrity of the pelvic floor.